Circulating Adaptive Immune Cells Expressing the Gut Homing Marker α4β7 Integrin Are Decreased in COVID-19 - Müller, Tanja; Becker, Elisabeth; Wiendl, Maximilian; Schulze, Lisa; Voskens, Caroline; Kremer, Andreas; Neurath, Markus; Zundler, Sebastian; Völkl, Simon (Frontiers in Immunology, 2021)
Background: Infection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a wide range of symptoms including gastrointestinal manifestations, and intestinal epithelial cells are a target of the virus. However, it is unknown how the intestinal immune system contributes to systemic immune responses in coronavirus disease 2019 (COVID-19). Methods: We characterized peripheral blood lymphocytes from patients with active COVID-19 and convalescent patients as well as healthy controls by flow cytometry. Results: The frequency and absolute number of circulating memory T and B cells expressing the gut homing integrin α4β7 integrin was reduced during COVID-19, whether gastrointestinal symptoms were present or not. While total IgA-expressing B cells were increased, gut-imprinted B cells with IgA expression were stable. Conclusion: COVID-19 is associated with a decrease in circulating adaptive immune cells expressing the key gut homing marker α4β7 suggesting that these cells are preferentially recruited to extra-intestinal tissues independently of α4β7 or that the systemic immune response against SARS-CoV-2 is at least numerically dominated by extraintestinal, particularly pulmonary, immune cell priming.
CRIS-Team Scopus Importer:2021-05-21
Keywords: COVID-19; gut homing; integrins; SARS-CoV-2 infection; T cell trafficking

Controlling in and out - the future of interfering with immune cell trafficking in inflammatory bowel disease - Zundler, Sebastian; Schulze, Lisa; Neurath, Markus (Expert Review of Clinical Immunology, 2022)
IntroductionImmune cell trafficking is a key requirement in the pathogenesis of inflammatory bowel diseases. Consistently, therapeutic strategies to target immune cell trafficking have been established and continue to be developed for the treatment of ulcerative colitis and Crohn's disease.Areas coveredIn this review, we briefly summarize the most important checkpoints of intestinal immune cell trafficking and their importance during IBD. Moreover, we provide an overview of associated therapeutic targets and previous as well as current efforts on treatment strategies related to these targets.Expert opinionFinally, we comment on potential future developments that might shape the field of immune cell trafficking in the context of IBD.
CRIS-Team WoS Importer:2023-01-06

Differential Effects of Ontamalimab Versus Vedolizumab on Immune Cell Trafficking in Intestinal Inflammation and Inflammatory Bowel Disease - Schulze, Lisa; Becker, Emily; Dedden, Mark; Liu, Lijuan; Van Passen, Chiara; Mohamed Abdou, Mariam; Müller, Tanja; Wiendl, Maximilian; Ullrich, Karen; Atreya, Imke; Leppkes, Moritz; Ekici, Arif Bülent; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: The anti-MAdCAM-1 antibody ontamalimab demonstrated efficacy in a phase II trial in ulcerative colitis and results of early terminated phase III trials are pending, but its precise mechanisms of action are still unclear. Thus, we explored the mechanisms of action of ontamalimab and compared it to the anti-α4β7 antibody vedolizumab. Methods: We studied MAdCAM-1 expression with RNA sequencing and immunohistochemistry. The mechanisms of action of ontamalimab were assessed with fluorescence microscopy, dynamic adhesion and rolling assays. We performed in vivo cell trafficking studies in mice and compared ontamalimab and vedolizumab surrogate [-s] antibodies in experimental models of colitis and wound healing. We analysed immune cell infiltration under anti-MAdCAM-1 and anti-α4β7 treatment by single-cell transcriptomics and studied compensatory trafficking pathways. Results: MAdCAM-1 expression was increased in active inflammatory bowel disease. Binding of ontamalimab to MAdCAM-1 induced the internalization of the complex. Functionally, ontamalimab blocked T cell adhesion similar to vedolizumab, but also inhibited L-selectin-dependent rolling of innate and adaptive immune cells. Despite conserved mechanisms in mice, the impact of ontamalimab-s and vedolizumab-s on experimental colitis and wound healing was similar. Single-cell RNA sequencing demonstrated enrichment of ontamalimab-s-treated lamina propria cells in specific clusters, and in vitro experiments indicated that redundant adhesion pathways are active in these cells. Conclusions: Ontamalimab has unique and broader mechanisms of action compared to vedolizumab. However, this seems to be compensated for by redundant cell trafficking circuits and leads to similar preclinical efficacy of anti-α4β7 and anti-MAdCAM-1 treatment. These results will be important for the interpretation of pending phase III data.
CRIS-Team Scopus Importer:2023-12-15

IL-3 receptor signalling suppresses chronic intestinal inflammation by controlling mechanobiology and tissue egress of regulatory T cells. - Ullrich, Karen; Derdau, Julia; Baltes, Carsten; Battistella, Alice; Rosso, Gonzalo; Uderhardt, Stefan; Schulze, Lisa; Liu, Lijuan; Dedden, Mark; Spocinska, Marta; Kainka, Lucina; Kubánková, Markéta; et al. (Gut, 2023)
IL-3 has been reported to be involved in various inflammatory disorders, but its role in inflammatory bowel disease (IBD) has not been addressed so far. Here, we determined IL-3 expression in samples from patients with IBD and studied the impact of Il3 or Il3r deficiency on T cell-dependent experimental colitis. We explored the mechanical, cytoskeletal and migratory properties of Il3r -/- and Il3r +/+ T cells using real-time deformability cytometry, atomic force microscopy, scanning electron microscopy, fluorescence recovery after photobleaching and in vitro and in vivo cell trafficking assays. We observed that, in patients with IBD, the levels of IL-3 in the inflamed mucosa were increased. In vivo, experimental chronic colitis on T cell transfer was exacerbated in the absence of Il-3 or Il-3r signalling. This was attributable to Il-3r signalling-induced changes in kinase phosphorylation and actin cytoskeleton structure, resulting in increased mechanical deformability and enhanced egress of Tregs from the inflamed colon mucosa. Similarly, IL-3 controlled mechanobiology in human Tregs and was associated with increased mucosal Treg abundance in patients with IBD. Collectively, our data reveal that IL-3 signaling exerts an important regulatory role at the interface of biophysical and migratory T cell features in intestinal inflammation and suggest that this might be an interesting target for future intervention.
EVALuna2:539503

Immune cell trafficking and retention in inflammatory bowel disease: Mechanistic insights and therapeutic advances - Zundler, Sebastian; Becker, Elisabeth; Schulze, Lisa; Neurath, Markus (Gut, 2019)
Intestinal immune cell trafficking has been identified as a central event in the pathogenesis of inflammatory bowel diseases (IBD). Intensive research on different aspects of the immune mechanisms controlling and controlled by T cell trafficking and retention has led to the approval of the anti-α4β7 antibody vedolizumab, the ongoing development of a number of further anti-trafficking agents (ATAs) such as the anti-β7 antibody etrolizumab or the anti-MAdCAM-1 antibody ontamalimab and the identification of potential future targets like G-protein coupled receptor 15. However, several aspects of the biology of immune cell trafficking and regarding the mechanism of action of ATAs are still unclear, for example, which impact these compounds have on the trafficking of non-lymphocyte populations like monocytes and how precisely these therapies differ with regard to their effect on immune cell subpopulations. This review will summarise recent advances of basic science in the field of intestinal immune cell trafficking and discuss these findings with regard to different pharmacological approaches from a translational perspective.
CRIS-Team Scopus Importer:2019-06-18
Keywords: cell adhesion; Crohn's disease; inflammatory bowel disease; integrins; ulcerative colitis

IMMUNOLOGY OF IL-12: AN UPDATE ON FUNCTIONAL ACTIVITIES AND IMPLICATIONS FOR DISEASE - Ullrich, Karen; Schulze, Lisa; Paap, Eva-Maria; Müller, Tanja; Neurath, Markus; Zundler, Sebastian (Excli Journal, 2020)
As its first identified member, Interleukin-12 (IL-12) named a whole family of cytokines. In response to pathogens, the heterodimeric protein, consisting of the two subunits p35 and p40, is secreted by phagocytic cells. Binding of IL-12 to the IL-12 receptor (IL-12R) on T and natural killer (NK) cells leads to signaling via signal transducer and activator of transcription 4 (STAT4) and subsequent interferon gamma (IFN-gamma) production and secretion. Signaling downstream of IFN-gamma includes activation of T-box transcription factor TBX21 (Tbet) and induces pro-inflammatory functions of T helper 1 (T(H)1) cells, thereby linking innate and adaptive immune responses. Initial views on the role of IL-12 and clinical efforts to translate them into therapeutic approaches had to be re-interpreted following the discovery of other members of the IL-12 family, such as IL-23, sharing a subunit with IL-12. However, the importance of IL-12 with regard to immune processes in the context of infection and (auto-) inflammation is still beyond doubt. In this review, we will provide an update on functional activities of IL-12 and their implications for disease. We will begin with a summary on structure and function of the cytokine itself as well as its receptor and outline the signal transduction and the transcriptional regulation of IL-12 secretion. In the second part of the review, we will depict the involvement of IL-12 in immune-mediated diseases and relevant experimental disease models, while also providing an outlook on potential translational approaches.
CRIS-Team WoS Importer:2021-01-15

Non-classical monocyte homing to the gut via α4β7 integrin mediates macrophage-dependent intestinal wound healing - Schleier, Lena; Wiendl, Maximilian; Heidbreder, Karin; Binder, Marie Theres; Atreya, Raja; Rath, Timo; Becker, Elisabeth; Schulz-Kuhnt, Anja; Stahl, Annette; Schulze, Lisa; Ullrich, Karen; Merz, Simon F.; et al. (Gut, 2019)
Objective: To study the role of α4β7 integrin for gut homing of monocytes and to explore the biological consequences of therapeutic α4β7 inhibition with regard to intestinal wound healing. Design: We studied the expression of homing markers on monocyte subsets in the peripheral blood and on macrophage subsets in the gut of patients with IBD and controls with flow cytometry and immunohistochemistry. Integrin function was addressed with dynamic adhesion assays and in vivo gut homing assays. In vivo wound healing was studied in mice deficient for or depleted of α4β7 integrin. Results: Classical and non-classical monocytes were clearly dichotomous regarding homing marker expression including relevant expression of α4β7 integrin on human and mouse non-classical monocytes but not on classical monocytes. Monocyte-expressed α4β7 integrin was functionally important for dynamic adhesion to mucosal vascular addressin cell adhesion molecule 1 and in vivo gut homing. Impaired α4β7-dependent gut homing was associated with reduced (effect size about 20%) and delayed wound healing and suppressed perilesional presence of wound healing macrophages. Non-classical monocytes in the peripheral blood were increased in patients with IBD under clinical treatment with vedolizumab. Conclusion: In addition to reported effects on lymphocytes, anti-α4β7 therapy in IBD also targets non-classical monocytes. Impaired gut homing of such monocytes might lead to a reduction of wound healing macrophages and could potentially explain increased rates of postoperative complications in vedolizumab-treated patients, which have been observed in some studies.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Crohn's disease; gut immunology; inflammatory bowel disease; surgery for IBD; ulcerative colitis